Workload and Work Environment as Determinants of Labor Productivity - Hamsal, Hamsal; Dianto, Iyoyo; Mardianti, Desy; Hidayat, Hidayat; Nuraini, Marina; Ningrum, Anggun Asminati (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to analyze the influence of workload and work environment on labor productivity at the Setia Kawan Cooperative Village Unit Office, Indragiri Hulu. The approach used is quantitative with purposive sampling techniques. Data was obtained through questionnaires to 80 respondents, then analyzed using SmartPLS 4 software to test the relationship between variables. The results of the study show that workload and work environment have a positive and significant effect on worker productivity. These findings affirm the importance of proportionate workload management and the creation of a conducive work environment in improving workforce performance. The limitation of this study lies in the scope that only covers one cooperative with a relatively small number of respondents, so the generalization of results is still limited. Further research is suggested to involve a broader sample as well as consider additional variables, such as motivation and leadership. This research makes an empirical contribution to the literature on the determinants of labor productivity, especially in the context of cooperatives in rural areas of Indonesia that are still rarely studied.